The Relationship Between Seller Ethical Habits, Customer Satisfaction, and Customer Trust and Loyalty - Ardiansyah Rasyid; Arifin Djakasaputra (Sultan Publisher, 2025)
Customer loyalty is a crucial driver for expanding market networks and sustaining business growth. Both loyalty and satisfaction form the foundation of customer relationship management (CRM), which is widely regarded as a strategic tool for achieving competitive advantage. Ethical sales practices have also been identified as vital in establishing and maintaining long-term customer relationships. This study collected data from 112 sportswear consumers selected through purposive sampling techniques. Data were obtained using a structured questionnaire, and the analysis was conducted using Structural Equation Modeling (SEM) with the SmartPLS software. The findings reveal that ethical sales behavior exerts a positive influence on customer satisfaction. Although ethical behavior also shows a positive but insignificant effect on customer loyalty, it significantly enhances customer trust. Furthermore, customer satisfaction significantly and positively influences customer loyalty, and customer trust also emerges as a significant determinant of loyalty. These results highlight the importance of ethical practices in building sustainable customer relationships.